ChemInform Abstract: Crystal Structure and Spectroscopic Studies of LiNH4(H2PO4)2 — A New Solid Acid in the LiH2PO4—NH4H2PO4 System. Issue 43 (October 2015) - Nguili, Narjess; Sunol, Joan Josep; Bulou, Alain; Toumi, Mohamed
Abstract LiNH4(H2PO4)2 is prepared from an equimolar aqueous mixture of NH4H2PO4 and LiH2PO4 by slow evaporation at 25 °C.